Terremoto, reconstrucción y reforma. Las cofradías limeñas frente al seísmo de 1746 - Lévano Medina, Diego (Pontificia Universidad Católica del Perú, 2022)
The earthquake of 1746 is an important milestone in Peruvian historiography because of its transcendence as a telluric movement and above all due to its impact from the economic, political and social points of view in the Peruvian society of the XVIII century. This article aims to provide a new vision through one of the most significant social bodies for the population of Lima at the time: the brotherhood. I address the role played by these corporations in the face of the earthquake and how they were affected materially and spiritually. Besides, how the process of material and administrati-ve reconstruction after the earthquake confronted them with the general reforms of these corporations promoted from the peninsula at the end of the 1750s.

El terremoto de 1746 es un hito importante en la historiografía peruana por su trascendencia como movimiento telúrico y sobre todo por su impacto desde el punto de vista económico, político y social en la sociedad peruana del siglo XVIII. Este artículo pretende aportar una nueva visión a través de uno de los cuerpos sociales más significativos para la población limeña de la época: la cofradía. Abordo el papel que cumplieron estas corporaciones frente al terremoto y cómo se vieron afectadas material y espiritualmente. Además, cómo el proceso de reconstrucción material y administrativo luego del terremoto las enfrentó a la reforma general de estas corporaciones impulsadas desde la península a finales de la década de 1750.
Earthquake, reconstruction and reform. The brotherhoods of Lima in the face of the earthquake of 1746
Keywords: Brotherhood; Confraternities; Earthquake of 1746; XVIII century; Lima; Cofradías; Hermandades; Terremoto de 1746; Siglo XVIII; Lima; https://purl.org/pe-repo/ocde/ford#6.00.00